2008
DOI: 10.1080/00223890802248828
|View full text |Cite
|
Sign up to set email alerts
|

Taxometric Analysis of the Levenson Self-Report Psychopathy Scale

Abstract: Levenson's Self-Report Psychopathy scale (Levenson, Kiehl, & Fitzpatrick, 1995) was administered to 1,972 male and female federal prison inmates, the results of which were subjected to taxometric analysis. We employed 4 taxometric procedures in this study: mean above minus below a cut (Meehl & Yonce, 1994), maximum slope (Grove & Meehl, 1993), maximum eigenvalue (Waller & Meehl, 1998), and latent-mode factor analysis (Waller & Meehl, 1998). The results showed consistent support for a dimensional interpretation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
1
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 30 publications
6
53
1
5
Order By: Relevance
“…These results contrast sharply with studies that found dimensionality underlying psychopathy, ASPD, and CD (Edens et al, , 2011Guay et al, 2007;Murrie et al, 2007;Walters, 2009;Walters et al, 2007aWalters et al, , 2007bWalters et al, , 2007cWalters et al, , 2008. This discrepancy may refl ect reliance on adult inmate or juvenile detention center samples in prior studies that overrepresented individuals with severe antisocial syndromes.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…These results contrast sharply with studies that found dimensionality underlying psychopathy, ASPD, and CD (Edens et al, , 2011Guay et al, 2007;Murrie et al, 2007;Walters, 2009;Walters et al, 2007aWalters et al, , 2007bWalters et al, , 2007cWalters et al, , 2008. This discrepancy may refl ect reliance on adult inmate or juvenile detention center samples in prior studies that overrepresented individuals with severe antisocial syndromes.…”
Section: Discussioncontrasting
confidence: 56%
“…Several clinical rating scales designed to assess psychopathy have been used in taxometric research, including various versions of the Psychopathology Checklist (PCL) and its revisions, the PCL-Revised and the PCL-Antisocial Process Screening Device (Frick and Hare, 2001;Hare 1993), antisocial subscales of the Personality Assessment Interview (Morey, 2007), and the Levenson Self-Report Psychopathology Scale (Levenson et al, 1995). Within this tradition, eight studies conducted among adult jail and/or prison inmates (Dana, 1990;Edens et al, 2006;Guay et al, 2007;Marcus et al, 2004;Walters, 2009;Walters et al, 2007aWalters et al, , 2007bWalters et al, , 2007cWalters et al, , 2008 and two studies (Edens et al, 2011;Murrie et al, 2007) conducted among adolescents in juvenile correctional facilities consistently yielded evidence of dimensionality of psychopathy.…”
mentioning
confidence: 99%
“…Each of these instruments also includes a factor denoting disturbed interpersonalaffective processing and a second one describing antisocial behavioral tendencies, although the exact content of these factors and their external correlates may differ for the different instruments (e.g., see Miller and Lynam, 2012, for an evaluation of the PPI Factor 1). Moreover, in each instrument each factor consists of a number of facets or subscales that are similar to the PCL-R facets (e.g., see Walters et al, 2008, for the four facets resulting from a principal components analysis of the LSRP). In the remainder of this paper, we will use the term 'Factor 1' in a general way to refer to items related to the fearless-dominance/interpersonal-affective factors.…”
Section: Psychopathy and Underlying Dimensionsmentioning
confidence: 99%
“…Os procedimentos taxométricos desenvolvidos por Meehl e seus colaboradores 11,13,14 têm sido amplamente empregados em estudos sobre a personalidade 15,16,17,18,19 , em estudos sobre esquizofrenia e experiências psicóticas 20,21 , demência 22 , psicopatia 23,24 , esquizotipia 25 , transtornos referentes ao uso do álcool e nicotina 26,27,28 , transtorno do déficit de atenção 29 , transtorno obsessivo-compulsivo 30 e transtornos alimentares 31 .…”
Section: Depressão; Envelhecimento; Avaliação Em Saúdeunclassified